2008
DOI: 10.1080/14631370802281373
|View full text |Cite
|
Sign up to set email alerts
|

Public attitudes toward business in contemporary Russia: influence of economic policy and opportunities for corporate response

Abstract: This article, based on public polls conducted in Russia in recent years and the analysis of relations among the state, business and society by Russian and foreign researchers, presents a step-by-step consideration of public opinion about business and the reasons for the formation of negative trends in this sphere; the influence of different aspects of economic policies (such as privatisation, tax policy, anti-monopoly policy and protection of consumers' rights, and combating corruption) on business activity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…As Chepurenko (2012) notices regarding Lerner (2009), the adequate programs are often implemented in rich countries with the Anglo-Saxon legal tradition. Negative public opinion and low confidence in the state support in Russia and other developing countries may decrease the possible positive effects of applying specific regional support programs such as free (special) economic zones (Yakovlev and Avraamova, 2008).…”
Section: Special Economic Zones and Small Businessmentioning
confidence: 99%
“…As Chepurenko (2012) notices regarding Lerner (2009), the adequate programs are often implemented in rich countries with the Anglo-Saxon legal tradition. Negative public opinion and low confidence in the state support in Russia and other developing countries may decrease the possible positive effects of applying specific regional support programs such as free (special) economic zones (Yakovlev and Avraamova, 2008).…”
Section: Special Economic Zones and Small Businessmentioning
confidence: 99%
“…More recent analyses of media discourses concerning business leaders indicated that authenticity, although praised, is often portrayed as incompatible with effectiveness (Iszatt‐White, Whittle, Gadelshina, & Mueller, ), thus implying that authenticity is a valued trait that nevertheless has no place in the business world. Views expressed in the media or cultural outlets may shape the public's general attitudes (Bateman, Sakano, & Fujita, ), and indeed some studies document public skepticism toward business in many cultures (Carroll, ; Yakovlev & Avraamova, ). The recent financial crisis has further increased skepticism about the role of business in society (Steckler & Clark, ).…”
Section: Introductionmentioning
confidence: 99%